ANALISIS TAGMEMIK KALIMAT TUNGGAL DALAM KUMPULAN CERPEN SENYUM KARYAMIN KARYA AHMAD TOHARI - Rien Helda Safitri; Patriantoro Patriantoro; Amriani Amir (Universitas Tanjungpura, 2019)
AbstractThis research was motivated by the role of single sentences in literature to build a short story. This study aimsed to present single sentence forms using tagmemics contained in the short stories of Senyum Karyamin. This research method was a descriptive method with qualitative research.The technique was used documentary technique. The data source in this study was a collection of short stories by Karyamin’s Smile by Ahmad Tohari. The data in this study were transitive active single sentences, active intransitive single sentences, and passive sentences. The technique of analyzing transitive active single sentence data, intransitive active single sentences and passive sentences used subordinate or gatra formulas, concluded the results of the analysis, and designs implementation into learning. Based on the results of data analysis it was found that the collection of short stories of Senyum Karyamin contained single sentence which were analyzed using tagmemics in the form of transitive single sentence, intransitive single sentence, and pasif single sentence. The number of use of each sentence in the short story collection was 78 transitive active single sentences, 122 intransitive active single sentences, and 4 passive single sentences. Keywords: tagmemics, short story